2006
DOI: 10.1001/jama.296.9.1063
|View full text |Cite
|
Sign up to set email alerts
|

Interns' Compliance With Accreditation Council for Graduate Medical Education Work-Hour Limits

Abstract: In the first year following implementation of the ACGME duty-hour standards, interns commonly reported noncompliance with these requirements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
82
0
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(84 citation statements)
references
References 14 publications
0
82
0
2
Order By: Relevance
“…Since studies of compliance with this work-hours regulation show that only a third of hospitals that have introduced compliance programs have actually used these programs to make the required change (Landrigan et al 2006), there must be a number of reasons for merely symbolic compliance. A claim that relational spaces are the only factor accounting for the difference in outcomes at these hospitals would not do justice to other possible conditioning factors that a comparative ethnographic study cannot detect.…”
Section: Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Since studies of compliance with this work-hours regulation show that only a third of hospitals that have introduced compliance programs have actually used these programs to make the required change (Landrigan et al 2006), there must be a number of reasons for merely symbolic compliance. A claim that relational spaces are the only factor accounting for the difference in outcomes at these hospitals would not do justice to other possible conditioning factors that a comparative ethnographic study cannot detect.…”
Section: Future Researchmentioning
confidence: 99%
“…Despite these new resources, at many hospitals residents did not use the programs that were established for their benefit. A recent study documents that compliance by interns with the 80-hour-workweek regulation (i.e., averaging 80 work hours per week or less each month) during 2003-4 occurred in only 33% of general surgery residency programs (Landrigan et al 2006). To put it differently, merely ceremonial compliance in surgery occurred in 67% of hospitals.…”
Section: Introductionmentioning
confidence: 99%
“…1 Resident well-being and patient safety were the main concerns relating to the excessive duty hours that residents sometimes worked prior to the 2003 changes. Even after these modifications, concerns remained about how compliant residents were with the duty hour rules, 2 and one rigorous study suggested that further reductions in maximum shift length could lead to safer patient care. 3 The Institute of Medicine (IOM) conducted an investigation in 2008 and published recommendations for further reductions in resident duty hours.…”
Section: Introductionmentioning
confidence: 99%
“…11,20 In the first year following implementation of the ACGME duty-hour standards, as many as 43% of interns reported noncompliance with these requirements. 21 This demonstrates that mandating work-hour reductions is only the first step in what is likely to be a long process of effecting change in nurse work hours and fatigue and, in turn, improving patient safety. However, initiating this process is going to be crucial, given the impact even small changes in nursing fatigue could have on patient-care outcomes.…”
Section: Discussionmentioning
confidence: 99%